Pemberdayaan Masyarakat Kampung Sidilem Melalui Kegiatan Budaya Cinta Lingkungan Demi Menciptakan Kepedulian Terhadap Lingkungan Sekitar - Dalilatul Muparikhah; Khairul Anam; Siti Aelina; Dimas Setiawan; Erna Septiana; Ilfatul Uyun; Annisa Nurul Fitri; Siti Romiza; Ofa Ari Oktavian (Pusat Pengabdian Kepada Masyarakat Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Community empowerment is one of the community's social research activities that contains social values ​​that are people-centered, participatory. Communities must be able to build social networks with the people around them in order to create a harmonious and peaceful life. The purpose of this research is to foster a sense of love and care for the people of Kampung Sidilem for the environment around them through the Culture of Love for the Environment or BCL. The research method used is a qualitative method with data obtained through interviews and supplemented by literature. The subjects of this research are the people of Kampung Sidilem. And the results of this study indicate that the people of Kampung Sidilem are at least able to understand their roles and functions in the community. So as to build a harmonious community life fabric.